The closed form solutions of simplified MCH equation and third extended fifth order nonlinear equation - Hossain, A.K.M. Kazi Sazzad; Akbar, M. Ali; Azad, Md. Abul Kalam (Propulsion and Power Research, 2019)
The investigation of closed form solutions for nonlinear evolution equations (NLEEs) is being an attractive subject in the different branches of mathematical and physical sciences. In this article, the enhanced (G′/G)-expansion method has been applied to find the closed form solutions for NLEEs, such as the simplified MCH equation and third extended fifth order nonlinear equations which are very important in mathematical physics. Plentiful closed form solutions with arbitrary parameters are successfully obtained by this method which are expressed in terms of hyperbolic and trigonometric functions. It is shown that the obtained solutions are more general and fresh and can be helpful to analyze the NLEES in mathematical physics and engineering problems.